1995
DOI: 10.1002/eji.1830250329
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12 profoundly up‐regulates the synthesis of antigen‐specific complement‐fixing IgG2a, IgG2b and IgG3 antibody subclasses in vivo

Abstract: The influence of the cytokine interleukin-12 (IL-12) on humoral immune responses was studied in vivo. CBA/J mice immunized with protein antigens (keyhole limpet hemocyanin, phospholipase A2) adsorbed to aluminum hydroxide (Alum) develop a Th2-like immune response characterized by the production of large amounts of IgG1 as well as some IgE but little IgG2a, IgG2b and IgG3 antibodies. IL-12 is a cytokine that promotes the development and the activation of Th1 cells. Th1 cells are involved in the induction of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
180
1
2

Year Published

1998
1998
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(195 citation statements)
references
References 62 publications
12
180
1
2
Order By: Relevance
“…These animals showed not only essentially identical patterns of increased susceptibility to mAb B6.1 when FNMS was used to replenish complement activity, but mAb C3.1 behaved in a similar fashion. mAb C3.1 is also a protective Ab with apparently identical epitope specificity as mAb B6.1, but mAb C3.1 is an IgG3 (23) and also should be a strong activator of complement (54). The acute lethality response was not due to metabolically active fungi, because formalin-killed yeast cells also caused the response.…”
Section: Discussionmentioning
confidence: 99%
“…These animals showed not only essentially identical patterns of increased susceptibility to mAb B6.1 when FNMS was used to replenish complement activity, but mAb C3.1 behaved in a similar fashion. mAb C3.1 is also a protective Ab with apparently identical epitope specificity as mAb B6.1, but mAb C3.1 is an IgG3 (23) and also should be a strong activator of complement (54). The acute lethality response was not due to metabolically active fungi, because formalin-killed yeast cells also caused the response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IL-12 can either enhance or inhibit humoral immunity, depending on the immunoglobulin isotype. Administration of recombinant IL-12 with protein Ag resulted in a significant increase of Th1-associated IgG2a, IgG2b, and IgG3 Ab response (36,37), whereas the Th2-associated IgG1 response was usually suppressed (38). In most studies of DNA vaccines, codelivery of the IL-12 gene was found to selectively increase IgG2a Ab, but had little effect or even decreased the total Ab titers (8, 39 -41).…”
Section: Figurementioning
confidence: 99%
“…Humoral immunity is also affected by IL-12. rmIL-12 decreases immunoglobulin G 1 (IgG 1 ) production and enhances the production of IgG 2a [16]. A major function of IL-12 seems to be in the defence against infectious diseases, especially those caused by intracellular microbes, this defence mechanism critically involves Th1 lymphocytes.…”
Section: Introductionmentioning
confidence: 99%